Islam and the Power of Logic - Irsyad Rauhillah Fa’iz; Dadan Firdaus; Nasywa Asyifa Salsabila; Siti Nurasyifa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses the relationship between Islam and logic through a qualitative approach, highlighting the concept of logic in Islamic theology and its role as a reasoning tool in Islamic philosophy. The research reveals how logic contributes to the development of Islamic law (fiqh) and facilitates dialog between Islamic thought and other intellectual traditions. By analyzing various perspectives, this article shows that logic is not only a tool of analysis, but also a bridge to understand and interpret Islamic teachings more deeply. Through this approach, it is hoped to strengthen the understanding of the importance of logic in religious and intellectual contexts